2008
DOI: 10.1183/09031936.00104407
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a cell phone-based exercise programme for COPD

Abstract: The application of a supervised endurance exercise training programme in a home setting offering convenience and prolonged effects is a challenge.In total, 48 patients were initially assessed by the incremental shuttle walk test (ISWT), spirometry and the Short Form-12 (SF-12) quality-of-life questionnaire, and then every 4 weeks for 3 months thereafter and again after 1 yr. During the first 3 months, 24 patients in the cell phone group were asked to perform daily endurance walking at 80% of their maximal capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
191
0
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(217 citation statements)
references
References 56 publications
7
191
0
10
Order By: Relevance
“…A recent study has shown that good compliance and adherence to the exercise programme for chronic obstructive pulmonary disease are additional factors that contribute to the maintenance of clinical benefits in the mobile telephone group during the self-management period [18]. This newly developed, innovative technique, the mobile telephone-based interactive self-care system, is a promising intervention to promote good communication between patients and caregivers, resulting in better adherence to asthma management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that good compliance and adherence to the exercise programme for chronic obstructive pulmonary disease are additional factors that contribute to the maintenance of clinical benefits in the mobile telephone group during the self-management period [18]. This newly developed, innovative technique, the mobile telephone-based interactive self-care system, is a promising intervention to promote good communication between patients and caregivers, resulting in better adherence to asthma management.…”
Section: Discussionmentioning
confidence: 99%
“…Through GPRS, many interactive functions can be created to provide instant access to information. In a recent study, a mobile telephone-based system was used to provide home endurance exercise training programme, and monitor respiratory symptoms and exercise activity with good compliance and clinical outcomes in patients with moderate-to-severe chronic obstructive pulmonary disease [18]. The success of this pilot study was encouraging enough to develop an automatic, interactive communication with asthmatic patients for self-monitoring and -management using mobile telephones.…”
mentioning
confidence: 99%
“…While pulmonary rehabilitation that includes supervised exercise training is efficacious (5), several factors limit the reach of this intervention (6). Moreover, pulmonary rehabilitation and exercise training have not been consistently associated with an increase in daily levels of physical activity (2)(3)(4)7), and there are very few trials of interventions to increase physical activity among patients with COPD compared with interventions of supervised exercise training (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…PR uygulanan KOAH'lı olgularda; 6 ve 12 dakika yürüme testleri, artan hızda mekik yürüme testi ve EMYT kullanılarak yapılan egzersiz kapasitesi değerlendirmelerinde, PR programı sonrasında yürüyüş mesafesinde anlamlı artış olduğu gözlen-miştir. [19][20][21][22][23][24] Liddell ve Webber, haftada iki kez göze-timli, bir kez evde olacak şekilde uygulanan PR programı sonucunda; AHMYT'de 50 m, EMYT süre-sinde 109 sn artış saptamışlardır. 25 Bizim PR uygulanan hastalarımızda AHMYT mesafesinde ortalama 75 m (%30,9); EMYT'deki egzersize dayanıklılık sü-resinde de 162 sn (%65,37) artış saptanmıştır.…”
Section: Discussionunclassified